2015
DOI: 10.1097/nmd.0000000000000287
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Early Interventions for Individuals at Clinical High Risk for Psychosis

Abstract: Youth and young adults at clinical high risk (CHR) for psychosis experience a broad range of difficulties, including attenuated psychotic symptoms, comorbid concerns, functional impairments, and family and interpersonal stress. Given emerging evidence that early interventions may improve functioning and reduce symptomatology while also lowering risk of transition to full-threshold psychosis, several randomized controlled trials have systematically evaluated the efficacy of CHR treatment approaches. This articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 0 publications
1
64
0
Order By: Relevance
“…The ultra-high risk (UHR) state is characterized by attenuated positive symptoms and/or a familial liability for psychotic disorders and by increased social isolation and functional decline. 2,3 In line with recent findings, [4][5][6][7][8] …”
Section: Introductionsupporting
confidence: 76%
“…The ultra-high risk (UHR) state is characterized by attenuated positive symptoms and/or a familial liability for psychotic disorders and by increased social isolation and functional decline. 2,3 In line with recent findings, [4][5][6][7][8] …”
Section: Introductionsupporting
confidence: 76%
“…Interventions that take a flexible approach to treatment could provide a model of care that can be tailored to the unique and dynamic needs of individuals at CHR by offering clinicians an array of evidence-based modules to use as needed to address psychosisspecific symptoms as well as co-occurring difficulties (Thompson et al, 2015). In line with the current findings, treatment modules focused on psychosis-risk could be complemented by strategies designed to address factors such as attention, locus of control, depression, and relationships with parents.…”
Section: Discussionmentioning
confidence: 99%
“…It is not possible to draw conclusions from the literature about the extent to which any practice is necessary or sufficient for improvements in treatment engagement . To draw those inferences would require the execution of dismantling studies.…”
Section: Discussionmentioning
confidence: 99%
“…Interventions that targeted caregivers of youth/young adults with CHR/FEP were included provided they met all other criteria. From this search, as well as a search of reference lists from review papers, [39][40][41] we identified 18 eligible studies published between 2002 and 2014 (see Table 2 for more details). [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] Coding…”
Section: Literature Searchmentioning
confidence: 99%